KAJIAN STRUKTURAL DALAM NOVEL BERJUDUL “KETIKA LAMPU BERWARNA MERAH” KARYA HAMSAD RANGKUTI DAN PEMANFAATANNYA SEBAGAI BAHAN AJAR MENGANALISIS UNSUR INTRINSIK KARYA FIKSI DI KELAS VIII SMP - Juwaira, Asna; Hasanah Harahap, Safinatul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the structural elements of the novel “Ketika Lampu Berwarna Merah” by Hamsad Rangkuti and to examine teachers perceptions regarding the use of regarding the use of teaching materials for analyzing the intrinsic elements of fiction in Grade VIII junior high school. This study employs a descriptive qualitative research approach, with data collected through document analysis and interviews. Data analysis was conducted using the content analysismethod developed by Miles and Huberman. The results indicate that the novel features a primary theme of parental love for a child and a secondary theme concerning the struggles of the urban poor. The narrative employs a mixed plot structure, featuring two main characters and eight supporting characters. The setting comprises fourteen location, with a timeframe spanning morning, midday, afternoon, and night. The social setting reflects the disparity between the rich and the poor. An omniscient third person point of view is used. The writing style incorporates similes, metaphors, and personification. The novels message emphasizes the importance of honesty, avoiding the abuse of power, mutual assistance, caring for others, perseverance, gratitude, and appreciating the kidness of others. The intrinsic elements are interconnected, forming a cohesive and meaningful story. Based on interviews with two teachers, the handout teaching materials were deemed suitable for use in Grade VIII Indonesian language instruction.